2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5160342
|View full text |Cite
|
Sign up to set email alerts
|

A modified Dubins method for optimal path planning of a Miniature Air Vehicle converging to a straight line path

Abstract: This paper presents a Dubins model based strategy to determine the optimal path of a Miniature Air Vehicle (MAV), constrained by a bounded turning rate, that would enable it to fly along a given straight line, starting from an arbitrary initial position and orientation. The method is then extended to meet the same objective in the presence of wind which has a magnitude comparable to the speed of the MAV. We use a modification of the Dubins' path method to obtain the complete optimal solution to this problem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In [13] an optimal path is computed to converge to a straight line starting from any initial configuration. Based on this result it can be shown that the γ-trajectory is the time-optimal trajectory that converges to the second waypoint segment starting from any start configuration on the first waypoint segment for γ ∈ [0, 1].…”
Section: A a General γ-Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…In [13] an optimal path is computed to converge to a straight line starting from any initial configuration. Based on this result it can be shown that the γ-trajectory is the time-optimal trajectory that converges to the second waypoint segment starting from any start configuration on the first waypoint segment for γ ∈ [0, 1].…”
Section: A a General γ-Trajectorymentioning
confidence: 99%
“…The proposed γ-trajectory takes minimum time to converge to the next waypoint segment starting from a point on the present waypoint segment. The trajectory generation is based on some results reported in rectilinear path convergence problem in [13]. A γ-trajectory is computed if the shortest distance between the waypoint and the trajectory is desired to be a certain value.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the final X position (X f ) is fixed and the final Y position (Y f ) is free. Dubins method was used for optimal path planning of miniature air vehicle converging to straight line in [4]- [6]. Way-point path following problems were discussed in [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…fixed-wing UAVs) previously entailed [1]. The common problem of wind, manifesting as both opportunity and hindrance for many UAVs, has spawned many contributions in the past [4], [2].…”
Section: Related Workmentioning
confidence: 99%